Settlement Analysis of a Confined Sand Aquifer Overlain by a Clay Layer due to Single Well Pumping. (10th March 2013) - Niu, Wen-jie; Wang, Zhenyu; Chen, Feng; Li, Hongran
Abstract : This paper proposes a simplified analytical solution to determine the primary consolidation settlement of a confined sand aquifer overlain by a clay layer due to single well dewatering. After single well pumping in a steady state, the Dupuit equation predicts the confined sand aquifer water head drawdown. The confining pressure on the underlain confined sand aquifer top surface is determined using the principle of vertical force equilibrium. Additional vertical stresses in each layer of the confined sand aquifer are then computed with the Boussinesq solution. The overall aquifer consolidation deformation is then determined with the e -lg p curve from the one-dimensional consolidation test and the applied vertical stress with the integral method. The proposed analytical solution is validated using the ADINA software, where porous media are simulated with the Biot model and solved with the 3D finite element method. This proposed analytical solution is used to simulate the primary consolidation settlement due to well pumping, using the fourth confined aquifer in the Pudong New Area of Shanghai from 1980 to 1995 as a case study. The predicted settlement compares reasonably well with the actual measured settlement in Shanghai.